Prowadzenie badań marketingowych w krajach UE : doświadczenia Instytutu Rynku Wewnętrznego i Konsumpcji w Warszawie - Olejniczuk-Merta, Anna (Conduct of Marketing Research in the European Union States Experience of the Institute of Internal Market and Consumption in Warsaw, 2006)
The paper presents a description of the research based on various phases of its execution. This serves as a background to show advantages and disadvantages which affect the final result of the research or at least its timing and smooth execution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 152-159